WOOL SHEARING PRACTICES AND GREASY FLEECE YIELD OF DECCANI SHEEP UNDER FIELD CONDITION IN TELANGANA REGION OF ANDHRA PRADESH* (Indian Journal of Animal Production and Management, 2013)
A survey was conducted to study the wool shearing practices of Deccani sheep followed by sheep farmers under filed condition and GFY in Telangana region of Andhra Pradesh. Majority (55.59%) of the sheep farmers shorn sheep twice (83.71 %) in a year manually by hired labour. Most (95.53%) of the farmers felt that no market was available for wool in the study area. Zone had significant (P
Keywords: Wool shearing practices; GFY; Deccani sheep; Telangana